ACUPRESSURE AND YOGA COMBINATION CAN REDUCE ANXIETY DURING PREGNANCY: A SYSTEMATIC REVIEW - Suwari, Ida Ayu Putu Dewi Adnya; Widyawati, Melyana Nurul; Anggraeni, Ni Putu Dian Ayu (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Untreated anxiety during pregnancy causes the health problems among mothers and the fetus. Complementary and Alternative Medicine (CAM) such as acupressure and yoga is seen as the alternatives to deal with this anxiety. This study aims to determine if the combination of acupressure and yoga is effective to reduce anxiety during pregnancy.Method: This study was a systematic review using the guidelines of the PRISMA. Articles were obtained from electronic databases Scopus, Science Direct, and PubMed by identifying published articles from January 2013 to March 2019. Articles were identified using keywords ?acupressure?, ?prenatal yoga?, and ?anxiety in pregnancy?. All articles included in this study were only those who used intervention research design in the form of an RCT and pilot study.Results: Ten of 1186 articles met the intended criteria in this study. The results showed that acupressure and yoga have significant benefits in reducing anxiety among pregnant women. It was also found that this combination potentially prevented the postpartum depression. Conclusion: Acupressure and yoga interventions can be combined as non-pharmacological therapy to reduce anxiety during pregnancy. Further research with more specific interventions is needed to provide evidence of reducing anxiety during pregnancy.